Aiming high, falling short: the Least Developed Country (LDC) category at 40 - Djalita Fialho (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Why have 94% of LDCs not escaped poverty during the last four decades? This paper analyses the motivation behind the UN decision to establish the LDC category in 1971. The reviewed literature highlights the conflicting interests of the actors involved. It provides a historical account of the creation of the category and an international political economy analysis of that process. Based on this literature, I argue that the initial LDC identification process - which set a precedent for future LDC categorizations - was manipulated in order to generate a reduced list of small and economically and politically insignificant countries. Contrary to the LDC official narrative, this list served the interests of both donors (by undermining the UN's implicit effort to normalize international assistance) and other non-LDC developing countries (disturbed by the creation of a positive discrimination within the group, favoring the most disadvantaged among them). As a result of this manipulation, considerably less development-promoting efforts have been demanded from donors, which has, in turn, not significantly distressed the interests of other non-LDC developing countries.
Keywords: N20; O19; 330; LDCs; aid; trade; preferential treatment; graduation